2018
DOI: 10.1055/s-0038-1636912
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Condyle Offset and Maximum Knee Flexion Following a Cruciate Retaining Total Knee Arthroplasty

Abstract: Inconsistent data has been reported on the effect of the femoral posterior condyle offset (PCO) on the maximal knee flexion after total knee arthroplasty (TKA). This study investigated the relationship between the postoperative changes of the PCO and the changes of maximal knee flexion after a cruciate retaining (CR) TKA. Nine patients with medial osteoarthritis (OA) in one knee were investigated. Before operation, each index knee was magnetic resonance imaging (MRI) scanned for construction of a three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…analyzed 268 patients who underwent robot‐assisted TKA and found that removing the same amount of bone from the distal and posterior femur resulted in an imbalance in the flexion–extension gap. Excessive external rotation and posterior condyle cuts may decrease the medial posterior condyle offset, which may affect maximal knee flexion 30,31 . Our findings indicate that more external rotation of the femoral component and more medial posterior femur bone resection may be needed in CR‐TKA.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…analyzed 268 patients who underwent robot‐assisted TKA and found that removing the same amount of bone from the distal and posterior femur resulted in an imbalance in the flexion–extension gap. Excessive external rotation and posterior condyle cuts may decrease the medial posterior condyle offset, which may affect maximal knee flexion 30,31 . Our findings indicate that more external rotation of the femoral component and more medial posterior femur bone resection may be needed in CR‐TKA.…”
Section: Discussionmentioning
confidence: 84%
“…Excessive external rotation and posterior condyle cuts may decrease the medial posterior condyle offset, which may affect maximal knee flexion. 30,31 Our findings indicate that more external rotation of the femoral component and more medial posterior femur bone resection may be needed in CR-TKA. By switching from a CR to PS prosthesis, less bone cutting may be required, and more bone mass might be preserved for these patients.…”
Section: Bone Resectionmentioning
confidence: 80%
“…This can also answer the question of whether uni ed low PSA osteotomy is reasonable at the present stage and whether individualized osteotomy should be established. Previous studies [9,10]generally only considered the single factor of PSA or PCO, and most did not consider the preoperative effect of both. With the deepening of cognition, it is more scienti c and rigorous to include the PCO and PSA of exion gap construction into the experiment and calculate the change amount to re ect the in uence on exion gap.…”
Section: Introductionmentioning
confidence: 99%